Guillain-Barré Syndrome following Treatment with Sunitinib Malate. (11th June 2014) - Kanaan, Ziad; Kulairi, Zain; Titianu, Mirela; Saha, Sandip; Kumar, Sarwan
Abstract : Sunitinib malate (Sutent, SU011248) is an oral multitargeted tyrosine kinase inhibitor (TKI) used for the treatment of metastatic renal cell carcinoma and imatinib (Gleevec)—resistant gastrointestinal stromal tumor (GIST) with few reported side effects including asthenia, myelosuppression, diarrhea, and mucositis. Scarce literature exists regarding the rare but often serious toxicities of sunitinib. Autoimmune and neurological side effects have been linked to sunitinib's inhibition of VEGF receptors with a corresponding increase in VEGF levels, which is associated with development of different neuropathies. We hereby report an interesting case of Guillain-Barré syndrome in a middle-aged patient with metastatic renal cell carcinoma following sunitinib treatment.